Russians in the newly undependent states: a comparative analysis between the cases of Kazakhstan, ukraine and the Baltic States - Alkan, Sevinç (My University, 2002)
The aim of this work is to discuss the sui generis position of the new Russian question among other post-Soviet nationality questions in a comparative analysis between the cases of Kazakhstan, Ukraine and the Baltic States - Estonia, Latvia, Lithuania - in terms of citizenship and minority rights that still remain unsettled questions in all the post-Soviet space which is also vulnerable to Russian state's sensitivity to Russians living abroad. These newly independent states, which were chosen for comparative analysis in this work, have significant amount of Russian minorities. In this work, first of all, the Soviet nationality policies and the Russians' socio-political position in the Soviet era, and then the impact of the new post-Soviet national question on the Russians of the depicted successor states will be examined, with due emphasis on the Soviet dual legacy during this still ongoing transition period. Russians' socio-political position and demography in the post- Soviet republics and the effects of minority policies of these republics (Kazakhstan, Ukraine, Baltics) on Russians are evaluated in the following chapters from the perspective of how national and ethnic relations are being reshaped in the post- Soviet states. As a sui generis group, the Russians still living in ex-Soviet lands no longer enjoyed the dominant position and became the new minorities in the newly independent states. These Russians living in former Soviet republics sometimes are referred to as Russians in the near abroad. In this reference while Russians reminded ethnic proximity the term near abroad has been used as an important part of new Russian foreign policy concerns by the Russian Federation. Therefore Russians in diaspora or Russians in the near abroad has been referred in Russia as one of the Russian Foreign policy objectives. Because of this reason in this work, the bilateral relations between Russian Federation and Kazakhstan, Ukraine, and the Baltics and how the minority policies of these states affect their foreign policies are examined in its own right. So the last chapter deals with the impact of the minorities issue on Russian domestic and foreign policies as well as on the foreign policies of Kazakhstan, Ukraine and the Baltic states in a comparative way. Bu çalışmanın amacı Sovyetler Birliği sonrası milliyet sorunları içerisinde sui generis (nev'i şahsına münhasır) bir pozisyona sahip olan yeni Rus sorununu, Kazakistan, Ukrayna ve Baltık Devletleri'nde (Estonya, Letonya, Litvanya) yaşayan Rusların vatandaşlık ve azınlık hakları ile Rusya Federasyonu'nun bu yeni azınlığa karşı gösterdiği duyarlılık çerçevesinde karşılaştırmalı olarak incelemektir. Söz konusu karşılaştırmalı analiz için seçilen yeni bağımsız devletlerde önemli oranda Rus azınlık bulunmaktadır. Bu çalışmada ilk olarak Sovyetler Birliği'nin milliyet politikaları, Rusların bu dönemdeki sosyo-politik durumları ile yeni bağımsız devletlerin geçiş döneminde karşılaştıkları milliyetler sorunu Sovyetler Birliği'nin bıraktığı ikili miras çerçevesinde incelenmektedir. Sovyetler Birliği'nin dağılmasından sonra yeni kurulan ülkelerde yaşayan Rusların sosyo-politik durumları ve demografik yapıları ile bu ülkelerin azınlık politikaları Sovyet sonrası dönemde yeniden şekillenen etnik ilişkiler çerçevesinde ileriki bölümlerde ele alınmaktadır. Sui generis bir grup olarak nitelendirebileceğimiz Ruslar, baskın pozisyonlarını kaybetmeye başlamış yeni bir azınlık grubu olarak eski Sovyet ülkelerinde yaşamlarını sürdürmektedirler. Rusya Federasyonu dışında yaşayan Ruslar zaman zaman yakın çevrede yaşayanlar olarak anılmaktadır. Bu referanstaki Ruslar kelimesiyle etnik yakınlık hatırlatılırken, yakın çevre kelimesiyle yeni Rus dış politika önceliklerinin önemli bir parçasına atıfta bulunulmaktadır. Sonuç olarak diasporadaki Ruslar ya da yakın çevredeki Ruslar tanımlamalarıyla Rus dış politika hedeflerinden biri kastedilmektedir. Bu nedenle bu çalışmada Rusya Federasyonu ile Kazakistan, Ukrayna ve Baltık Devletleri arasındaki ilişkiler, ayrıca bu ülkelerin azınlık politikalarının tarafların dış politikalarını nasıl etkilediği ayrı bir bölümde incelenmektedir. Son bölümde ise bu üç yeni bağımsız ülkedeki Rusların sosyo-ekonomik durumu ve bu ülkelerin azınlık hakları sorununun bu ülkelerin iç ve dış politikalarına olduğu kadar Rus iç ve dış politikasına etkileri karşılaştırmalı olarak ele alınmaktadır
Keywords: Azınlıklar_Rusya; Kazakistan_Siyaset ve Yönetim; Ukrayna_Siyaset ve Yönetim